Split Sentencing and the "Youth Discount" in Florida Criminal Courts - Lehmann, Peter S. (Crime & delinquency, 2024)
Prior research on the criminal court punishment of transferred youth relative to adult defendants has produced mixed findings; however, these disparities have not been examined in the context of intermediate and alternative sanctions. In Florida, judges have the discretion to assign a split sentence, which involves a mitigated term of imprisonment followed by a sentence to community supervision. Using data on felony cases sentenced under Florida?s Criminal Punishment Code (N?=?704,977), these results provide evidence of a ?youth discount,? with juveniles more likely than adults to receive split sentences. However, this pattern is observed regardless of whether a prison sentence is recommended by the guidelines, that is, even among cases in which a split sentence represents an upward departure.